Pain Management and Homeopathy (Homoeopathy for All, 2023)
Understanding Homeopathy:  Homeopathy is a form of alternative  medicine developed in the late 18th  century by Samuel Hahnemann. It is  based on the principle of “like cures  like,” which means that a substance  that causes symptoms in a healthy  person can be used in diluted form  to treat similar symptoms in an  individual suffering from an illness.  Homeopathic remedies are prepared  through a process of potentization,  which involves diluting a substance  multiple times and vigorously  shaking it. The underlying belief  is that this process enhances the  healing properties while minimizing  any potential toxicity.
Keywords: Homeopathy; potentization; toxicity